THE RELATIONSHIP BETWEEN ENGLISH TIKTOK VIDEO ENGAGEMENT AND SELF-DIRECTED VOCABULARY LEARNING AMONG EFL UNIVERSITY STUDENTS - Syarifah Soraya; Yasmine Mumtaazah; Fitriyah; Najwa Amalia; Abdul Syahid (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2026)
The increasing prevalence of short-form video platforms has expanded opportunities for informal English learning beyond traditional classroom settings. Among these platforms, TikTok has gained increasing scholarly attention due to its microlearning features and high levels of student engagement. However, empirical evidence linking TikTok engagement to self-directed vocabulary learning remains limited. This study investigates the relationship between EFL university students’ engagement with English TikTok videos and their self-directed vocabulary learning. Using a quantitative correlational design, the study involved 86 undergraduate EFL students from a state university in Palangka Raya, Indonesia. Data were collected through two validated instruments: the Self-Directed Vocabulary Learning Scale, measuring goal-setting, self-monitoring, and self-evaluation, and the TikTok Video Engagement Scale, assessing behavioural, affective, and cognitive engagement. Descriptive statistics and Pearson’s product-moment correlation analysis were employed. The findings revealed significant positive correlations between all dimensions of TikTok engagement and self-directed vocabulary learning (r = .445–.674, p <.001). Affective and cognitive engagement showed the strongest relationships with self-monitoring and self-evaluation. These results indicate that engagement with English-language TikTok videos is positively associated with learners’ autonomous vocabulary development. The study highlights the pedagogical potential of social media–based microlearning to support learner autonomy and vocabulary acquisition in the higher education EFL contexts.